Long-term evolution of three operated patients of rectal cancer via the York Mason line - Praderi, Raúl C; Harretche, Martín (Cirugía del Uruguay, 1998)
Before the development of mechanical suture machines, we often used the York Mason transrectal approach technique for resection of viflious tumors of the rectum and small carcinomas.